High-performance WO3−x-WSe2/SiO2/n-Si heterojunction near-infrared photodetector via a homo-doping strategy. Issue 21 (23rd May 2018) - Guo, Tianchao; Ling, Cuicui; Zhang, Teng; Li, Hui; Li, Xiaofang; Chang, Xiao; Zhu, Lei; Zhao, Lin; Xue, Qingzhong
Abstract : The enhanced performance of WO3− x -WSe2 /SiO2 /n-Si can be mainly attributed to the down-shift of the E F of WO3− x -WSe2, which results in a larger interface barrier height and a greatly reduced dark current. Abstract : It is demonstrated that homo-doping is a simple and effective strategy to improve near-infrared (NIR) photoresponsive performance of a WO3− x -WSe2 /SiO2 /n-Si heterojunction. Our systematic studies showed that an air thermal annealing treatment can enrich the p-WO3− x dopants of WSe2, which was essential to greatly enhance the NIR photoresponsive performance of the WO3− x -WSe2 /SiO2 /n-Si heterojunction. Moreover, this heterojunction exhibited excellent selectivity and good stability to the incident light of 900 nm with high photoresponsivity of ∼137.7 A W −1, superior detectivity ( D* ) of ∼2.27 × 10 14 Jones (1 Jones = 1 cm Hz 1/2 W −1 ), and prominent sensitivity ( S ) of ∼1.19 × 10 8 cm 2 W −1 . When compared with the WSe2 /SiO2 /n-Si heterojunction, D* was increased by a factor of 7 and S was enhanced by a factor of 35. Comprehensive performance analyses indicate that the device fabricated in this work is not only significantly better than most of the reported Si based devices, but also can be comparable with 0D and 2D based nanostructure heterojunction devices. Systematic NIR photoresponsive studies demonstrate that the enhanced photoresponsive performance can be mainly attributed to the down-shift of the Fermi level of p–p homo-doped WO3− x -WSe2, which generates the larger interface barrier height between WO3− x -WSe2 and n-Si and the weaker dark current of the p–p homo-doped WO3− x -WSe2 /SiO2 /n-Si heterojunction. Our studies demonstrate that the homo-doping approach may be extended to fundamentally modify other semiconductor based photodetectors.